HOME-SCHOOL TASKS SPILLOVER AND PROFESSIONALISM OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN THE DISTRICT OF CUARTERO - Hallegado, Shermen H. (IDEAS: Journal of Management & Technology, 2024)
The study aimed to determine the extent of home-school tasks spillover and degree ofprofessionalism of public elementary school teachers in the District of Cuartero in the schoolyear 2023-2024. A validated and reliability tested researcher-made questionnaire was used togather the needed data from randomly selected respondents. The statistical tools used toanalyze and interpret the gathered data were frequency count, percentage, mean, t-test, F- test,and Pearson r. The findings of the study revealed that the extent of home-school tasks spilloveras a whole and in terms of emotional well-being and family dynamics was very high. The degreeof professionalism as a whole and in terms of work engagement and social interactions wasalso found to be very high. No significant differences were found on home- school tasksspillover of the respondents when grouped according to sex, age, and length of service.However, a significant difference was noted when grouped according to status. There was nosignificant difference in the professionalism of the respondents when grouped according to sex,age, status, and length of service. The extent of home-school tasks spillover andprofessionalism of the respondents were significantly related. The results indicated that thehome-school tasks spillover significantly influence the professionalism of teachers. This meansthat the higher is the extent of home-school tasks spillover, the lower is the degree ofprofessionalism of public elementary school teachers and vice versa. When the teachers havemore tasks spillover at home or school, the lower is their degree of professionalism becausethey handle the task well and proper. It further means that the teachers know how to balancetheir time and have positive outlook in their personal, social and professional life.